Global smoking‐attributable burden of periodontal disease in 186 countries in the year 2015. (21st November 2017) - Schwendicke, Falk; Dörfer, Christof E.; Meier, Toni
Abstract: Aim: We aimed to quantify the smoking‐attributable burden of periodontal disease (PD). Methods: The association between smoking and PD was evaluated. Population, smoking and PD data from the Global Burden of Disease Study were used, and the burden in different sex and age groups in 186 countries in 2015 calculated, adjusted for PD prevalence and numbers of cigarettes smoked. No adjustment was performed in a sensitivity analysis. Results: The global smoking‐attributable burden was 251, 160 disability‐adjusted life years (DALYs; 95% uncertainty interval: 190, 721–324, 241; sensitivity analysis: 344, 041 DALYs) or 38.5 million cases. The burden was lower in females than males, and highest in the age group of the 50‐ to 69‐year‐olds. On super‐regional level, the burden was highest in South‐East Asia, East Asia and Oceania (83, 052 DALYs), and high‐income North America and Asia Pacific (55, 362 DALYs). On regional level, it was highest in East Asia (70, 845 DALYs), South Asia (30, 808 DALYs) and North Africa and the Middle East (24, 095 DALYs). On national level, it was highest in China (69, 148 DALYs), India (29, 362 DALYs) and the United States (12, 714 DALYs). The relative smoking‐attributable burden ranged between >25% in Suriname and <1% in Chad. Conclusions: There is great need to monitor and tackle the smoking‐attributable burden of PD.